Metal matrix nanocomposites and their application in corrosion control - Gupta P.; Kumar D.; Quraishi M.A.; Parkash O. (My University, 2025)
The present chapter gives an overview of nanocomposites which are novel materials for corrosion control. Nanocomposites comprise of more than one phase where size of each phase is less than 100 nm respectively. There are basically three types of nanocomposites: Ceramic-Matrix Nanocomposites, Metal-Matrix Nanocomposites and Polymer Matrix Nanocomposites. Several synthesis routes have been proposed for the fabrication of MMNCs such as Stir Casting, Powder Metallurgy, CVD, PVD etc. Major applications of metal matrix nanocomposites are in automobile and aerospace industries. Among various properties corrosion is an important property for determining the life expectancy of any nanocomposite material. In the present chapter a brief account of corrosion and its control using nanocomposites has been discussed. It is expected that the present chapter will help the readers to get a glimpse of nanocomposite materials for its wider use in industrial applications. © Springer India 2016.